Implementation of the Symptom Navi © Programme for cancer patients in the Swiss outpatient setting: a study protocol for a cluster randomised pilot study (Symptom Navi© Pilot Study). Issue 7 (9th July 2019) - Bana, Marika; Ribi, Karin; Kropf-Staub, Susanne; Zürcher-Florin, Sabin; Näf, Ernst; Manser, Tanja; Bütikofer, Lukas; Rintelen, Felix; Peters, Solange; Eicher, Manuela
Abstract : Introduction: Self-management interventions show promising results on symptom outcomes and self-management behaviours. The Symptom Navi© Programme (SN©P) is a nurse-led intervention supporting patients' symptom self-management during anticancer treatment. It consists of written patient information (Symptom Navi© Flyers (SN©Flyers)), semistructured consultations and a training manual for nurses. Methods and analysis: This pilot study will evaluate the implementation of the SN©P based on the Reach Effectiveness—Adoption Implementation Maintenance framework at Swiss outpatient cancer centres. We will use a cluster-randomised design and randomise the nine participating centres to the intervention or usual care group. We expect to include 140 adult cancer patients receiving first-line systemic anticancer treatment. Trained nurses at the intervention clusters will provide at least two semistructured consultations with the involvement of SN©Flyers. Outcomes include patients' accrual and retention rates, patient-reported interference of symptoms with daily functions, symptom burden, perceived self-efficacy, quality of nursing care, nurse-reported facilitators and barriers of adopting the programme, nurses' fidelity of providing the intervention as intended, and patients' safety (patients timely reporting of severe symptoms). We will use validated questionnaires for patient-reported outcomes, focus group interviews with nurses and individual interviews with oncologists. Linear mixed models will be used to analyse patient-reported outcomes. Focus group and individual interviews will be analysed by thematic analysis. Ethics and dissemination: The Symptom Navi© Pilot Study has been reviewed and approved by Swiss Ethic Committee Bern (KEK-BE: 2017–00020). Results of the study will be disseminated in peer-reviewed journal and at scientific conferences. Trial registration number: NCT03649984 ; Pre-results.